2011
DOI: 10.2460/javma.238.12.1634
|View full text |Cite
|
Sign up to set email alerts
|

Epiglottic abnormalities in mature nonracehorses: 23 cases (1990–2009)

Abstract: Results suggested that coughing is a common complaint in mature nonracehorses with epiglottic abnormalities. Therefore, upper airway endoscopy is recommended in the evaluation of older horses with a cough. Surgical treatment can be beneficial in most horses, with some requiring further postoperative medical treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
17
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 15 publications
0
17
0
1
Order By: Relevance
“…In contrast with the present study, Tulleners () reported that all 10 horses with SECs demonstrated respiratory noise, with additional complaints of coughing (30%), exercise intolerance (20%) and dysphagia (20%). Furthermore a study investigating epiglottic abnormalities in mature nonracehorses reported clinical signs of coughing (n = 2) and dysphagia (n = 1) in 3 horses with SECs (Aitken and Parente ). The discrepancy in prevalence of clinical signs seen in this case series compared to others is likely to be due to the difference in age of the study populations, with our population being generally younger.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In contrast with the present study, Tulleners () reported that all 10 horses with SECs demonstrated respiratory noise, with additional complaints of coughing (30%), exercise intolerance (20%) and dysphagia (20%). Furthermore a study investigating epiglottic abnormalities in mature nonracehorses reported clinical signs of coughing (n = 2) and dysphagia (n = 1) in 3 horses with SECs (Aitken and Parente ). The discrepancy in prevalence of clinical signs seen in this case series compared to others is likely to be due to the difference in age of the study populations, with our population being generally younger.…”
Section: Discussionmentioning
confidence: 99%
“…). However, it has also been reported that SECs may be acquired secondary to inflammation or trauma and they are occasionally found in older horses with no previous history of upper respiratory tract problems (Davenport‐Goodall and Parente ; Aitken and Parente ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Persistent epiglottic entrapment (EE) is a common abnormality in the racehorse and the mature nonracehorse . EE affects 0.9%‐3% of thoroughbred racehorses examined for suspected upper respiratory obstruction, resulting in clinical signs of exercise intolerance, poor performance, respiratory noise, and coughing .…”
Section: Introductionmentioning
confidence: 99%
“…However, when elongation of the soft palate occurs the epiglottis is lying ventral to the soft palate and it is therefore completely lost from the observer's view. 34 Rostral displacement of the palatopharyngeal arch (RDPA), over one or both of the corniculate processes of the arytenoids that appears malformed, does not abduct well, or both. Abnormal arytenoid movement in most cases might be a result of abnormal anatomy of laryngeal cartilages and muscles, not restriction by the palatopharyngeal arch.…”
mentioning
confidence: 99%